Evaluation of Structural Effects of Acyclic and Macrocyclic Ligands Derived from (R,R)-Cyclohexane-1,2-diamine in the Enantioselective Cu(II)-Catalyzed Henry Reaction - Cerisoli, Lucia; Grilli, Stefano; Savoia, Diego (Letters in Organic Chemistry, 2014)
Two new ligands with acyclic or macrocyclic structure were prepared from (R,R)-cyclohexane-1,2-diamine, the former by condensation with 5-[1-methyl-1-(1H-pyrrol-2-yl)ethyl]-1H-pyrrole-2-carboxaldehyde, and the latter by double condensation with 5,5'-(1H-pyrrole-2,5-diyl)bis(furan-2-carboxaldehyde). Subsequent reduction of the intermediate diimine and tetraimine with sodium borohydride afforded the corresponding amines, which were tested as ligands in the Henry reaction of benzaldehyde with nitromethane. The results were compared with those obtained by analogous acyclic and macrocyclic ligands and enabled to assess that the macrocyclic structure of pyrrole-containing ligand was beneficial for achieving high enantioselectivity. Moreover, it was confirmed that the asymmetric induction of ligands containing the pyrrole ring, even if a furan ring is also present, is opposite to that displayed by analogous furan- and thiophenecontaining ligands with the same chirality of the cyclohexane-1,2-diamine moiety.
Keywords: pyrrole